2017
DOI: 10.1177/1010539517699060
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Workplace Exposures on Quality of Life in Small and Medium Enterprises Workers: A Cross-Sectional Study in Four ASEAN Countries

Abstract: Quality of life is associated with several factors, including personal living styles and working conditions. This article aims to investigate the factors associated with quality of life among small and medium enterprises (SME) workers in 4 countries of the Association of Southeast Asian Nations (ASEAN), namely Malaysia, Indonesia, Thailand, and Vietnam. A total of 2014 workers from food and textile industries were asked to answer a questionnaire about their sociodemographic characteristics, working environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…Four studies from Japan [ 62 , 64 , 65 , 66 ] seemed to use data from the same survey but examined different outcomes. No studies from Africa or South America met our inclusion criteria, and four studies were transnational [ 61 , 75 , 76 , 77 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Four studies from Japan [ 62 , 64 , 65 , 66 ] seemed to use data from the same survey but examined different outcomes. No studies from Africa or South America met our inclusion criteria, and four studies were transnational [ 61 , 75 , 76 , 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…The work characteristics ‘working environment’ and ‘new forms of work’ have received less attention. Only three studies measured physiochemical factors: ‘lighting’ was measured by two studies [ 29 , 75 ], ‘climate’ was measured only by Isahak et al [ 75 ]. Rhee et al [ 76 ] assessed the variables ”hazardous work condition” and “handling of hazardous materials”.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the results of the quality of life measurements can be taken as the consideration in redesigning work facilities, adjusting workload and employee work performance, evaluating employee and company productivity. In addition to physical, psychological, social and environmental factors, other in-line research on quality of life has been reported that quality of life can be influenced by lifestyle, work characteristics and workplace conditions particularly in workers in the food and textile industries [18], socio-demographic factors, job characteristics, individual characteristics and lifestyle [19]. Coverage in the quality of life assessment requires a more holistic instrument in order to respond to the various needs of respondents.…”
Section: Icohs 2017mentioning
confidence: 99%